Metastasis-related methyltransferase 1 (Merm1) represses the methyltransferase activity of Dnmt3a and facilitates RNA polymerase I transcriptional elongation. (21st March 2018) - Lyu, Guoliang; Zong, Le; Zhang, Chao; Huang, Xiaoke; Xie, Wenbing; Fang, Junnan; Guan, Yiting; Zhang, Lijun; Ni, Ting; Gu, Jun; Tao, Wei
Abstract: Stimulatory regulators for DNA methyltransferase activity, such as Dnmt3L and some Dnmt3b isoforms, affect DNA methylation patterns, thereby maintaining gene body methylation and maternal methylation imprinting, as well as the methylation landscape of pluripotent cells. Here we show that metastasis-related methyltransferase 1 (Merm1), a protein deleted in individuals with Williams–Beuren syndrome, acts as a repressive regulator of Dnmt3a. Merm1 interacts with Dnmt3a and represses its methyltransferase activity with the requirement of the binding motif for S-adenosyl-L-methionine. Functional analysis of gene regulation revealed that Merm1 is capable of maintaining hypomethylated rRNA gene bodies and co-localizes with RNA polymerase I in the nucleolus. Dnmt3a recruits Merm1, and in return, Merm1 ensures the binding of Dnmt3a to hypomethylated gene bodies. Such interplay between Dnmt3a and Merm1 facilitates transcriptional elongation by RNA polymerase I. Our findings reveal a repressive factor for Dnmt3a and uncover a molecular mechanism underlying transcriptional elongation of rRNA genes.